EVALUATION OF PROTEOLYTIC ACTIVITY IN EXPERIMENTAL PERITONITIS WITH SEROGUARD® TREATMENT - M.G. SHURYGIN; S.L. BOGORODSKAYA; E.E. CHEPURNYKH; L.V. RODIONOVA; L.G. SAMOYLOVA; I.A. SHURYGINA (Avicenna Tajik State Medical University, 2024)
Objective: Study the proteolytic activity during experimental peritonitis using Seroguard® as a local anti-inflammatory agent Methods: The experiment involved male Wistar rats aged 6 months. The researchers induced experimental peritonitis in the animals using a specific technique they developed. In the control group (n=20), the rats were given an intraperitoneal injection of 3 ml of saline one day after simulating peritonitis. The experimental group (n=19) received the same volume of the Seroguard® solution (JSC Pharmasyntez, Russia), a prolonged form of the p38 MAPK inhibitor. Healthy age-matched rats (n=7) are used to determine indicators typical for intact animals. Total protein and low molecular weight proteins (LMWP) in liver homogenates were determined using the modified Lowry protein assay, and serum total protein and albumin were measured using kits purchased from BioSystems S.A. (Costa Brava, Spain) Results: The experimental peritonitis significantly impacted the levels of LMWP in the liver tissue. A statistically significant increase in their accumulation in the group with purulent peritonitis was observed when Seroguard® was not administered throughout the study period. However, a single administration of the Seroguard® reduced the severity of proteolytic reactions in peritonitis. Additionally, Seroguard® led to a temporary inhibition of albumin synthesis by hepatocytes for up to 3 days, followed by compensation by the 7th day of observation Conclusion: Diffuse purulent peritonitis is characterized by significant activation of proteolytic processes and the accumulation of proteolysis products in the liver. Seroguard® inhibited the increase in proteolysis activity. When administered as a single injection into the abdominal cavity on the first day of simulating a purulent inflammatory process, this effect is more noticeable in the initial stages of observation. Reducing the production of proteolysis products may play a significant role in therapy to decrease the risk of developing multiorgan failure in peritonitis. However, the observed decrease in albumin production in the initial days after drug administration in the settings of extensive peritoneal damage should be a focus of clinical studies to assess the safety of the drug in this pathology